Brexit: What now for Study Mobility between the UK and the EU? - James, Cherry (Pécs journal of international and European law, 2016)
In the referendum held on 23 June 2016 the UK voted to leave the EU. This momentous change is unlikely to come to pass for some time, but has significant implications for study mobility between the UK and the EU. The article considers the legal position of UK national degree mobile students studying in EU member states and EU national degree mobile students studying in the UK, and how EU law developed to encompass and facilitate such mobility. Different ways in which the current position may change are then considered, depending on whether the UK does or does not remain in the EEA or adopts a Swiss style relationship with the EU. The focus then turns to credit mobility and in particular, credit mobility under the aegis of the Erasmus Programme. The development and operation of the Erasmus Programme is explained and again the prospects for the UK’s continued participation in the Erasmus Programme are considered on the basis of differing potential post-Brexit relationships between the UK and the EU.